AB1067 Suitability of cadaver models in ultrasound diagnostics and interventions in rheumatology: foot and ankle. (15th June 2017) - Halász, V; Nemeskéri, Ά; Bong, D; Mandl, P; Möller, I; Naredo, E; Bálint, PV; ,
Abstract : Background: Employment of cadaver specimens in ultrasonography provides a useful and safe model for education, enhances the anatomical knowledge of sonographers and may help determine the accuracy of ultrasound-guided interventions. Objectives: In this systemic literature review (SLR) we assessed the role and use of cadaver specimens in sonographic studies of the foot and ankle in the field of rheumatology. Methods: For our literature review we utilized the MEDLINE database, which were supplemented by searches in Google Scholar and Science Direct when the articles were not available through PubMed. Original studies in English language were included in the full paper review with an exception of three German language studies with English abstracts were also included. In the full paper review studies were selected for inclusion featured the sonographic study of cadaver specimens of the foot and ankle. Data were extracted on study characteristics and interventions. Results: The search yielded 1241 articles, of which 130 were selected for detailed review. In the end, 23 full papers met inclusion criteria. The studies could be grouped as follows: description of detailed ultrasound anatomy (9), testing of accuracy of ultrasound guided interventional procedures (8), examination of artificial tears and lesions (4), foreign bodies (1) and joint effusions (1). The results that were obtained in the studies of the fully reviewed papers utilized a total of 294 cadaveric specimens, with an average of 12.78 (range: 1–48) cadaveric specimens included in each study. Conclusions: The use of cadaver specimens of the foot and ankle may facilitate the validation of new sonographic methods which assess these joint regions, however the major disadvantage of these studies was the low number of cadaveric specimens. Disclosure of Interest: None declared